Efeitos sedativo e cardiorrespiratório da administração da metadona, isoladamente ou em associação à acepromazina ou xilazina, em gatos - Monteiro, Eduardo Raposo; Picoli, Fabricia Mateus; Queiroz, Marisa Guizeline de Oliveira; Campagnol, Daniela [UNESP]; Quitzan, Juliany Gomes [UNESP] (My University, 2008)
Six cats weighting 3.3±0.3 kg were randomly allocated to 6 treatments, with at least one-week intervals. The cats received intramuscular administration of physiological saline (control), methadone (0.3 mg/ kg), acepromazine (0,1 mg/kg), xylazine (1.0 mg/kg), acepromazine (0.05 mg/kg) plus methadone (0.3 mg/kg) or xylazine (0.5 mg/kg) plus methadone (0.3 mg/kg). Heart rate (HR), respiratory rate (RR), indirect systolic arterial pressure (SAP), rectal temperature, sedation score and pedal withdrawal reflex were evaluated before (baseline) and at selected intervals after treatment administration for 90 minutes. Respiratory rate, HR and rectal temperature decreased in cats given xylazine or xylazine plus methadone. In 1 out of 6 cats given xylazine and 2 out of 6 cats given xylazine/methadone, pedal withdrawal reflex was absent. In cats given 0.1 mg/kg of acepromazine, SAP decreased compared to baseline. Sedation scores were greater in cats given xylazine or xylazine plus methadone. Methadone alone or in combination with acepromazine did not produce a satisfactory degree of sedation and resulted in signs of excitement in some of the cats. Methadone alone or combination with acepromazine was not considered an effective protocol when moderate to deep sedation is required in cats. Methadone in combination with xylazine produces moderate to deep sedation, being this effect comparable to that achieved with a higher dose of xylazine alone.
Sedative and cardiorespiratory effects of methadone, alone or in combination with acepromazine or xylazine, in cats
Keywords: Acepromazine; Cat; Methadone; Sedation; Xylazine